Link-first based quick coordinated virtual network embedding algorithm - Wen-cheng XIONG; Ying WANG; Xue-song QIU; Wen-jing LI (Tongxin xuebao)
In order to reduce costs of link embedding and increase revenue, a coordinated embedding algorithm based on link-first is proposed. The algorithm embeds link and node alternately, and embeds the virtual link that with greater band-width requirement first to the physical path that with fewer link hops by using the greedy method, and ultimately aims at re-ducing average costs of virtual network embedding and improving acceptance rate of virtual network. Simulation results show that, compared with the existing algorithms, this embedding algorithm saves link cost significantly, improves accep-tance rate of virtual network and revenue of the physical network, and can effectively shorten the running time.